Upregulation of Transient Receptor Potential Vanilloid Type-1 Channel Activity and Ca2+ Influx Dysfunction in Human Pterygial Cells - Garreis, Fabian; Schröder, Antje; Reinach, Peter S.; Zoll, Stefanie; Khajavi, Noushafarin; Dhandapani, Priyavathi; Lucius, Alexander; Pleyer, Uwe; Paulsen, Friedrich; Mergler, Stefan (Investigative Ophthalmology & Visual Science, 2016)
PURPOSE: The heat-sensitive transient receptor potential vanilloid type-1 (TRPV1) channel (i.e., capsaicin [CAP] receptor) is upregulated in numerous cancers. This study determined if this response occurs in fresh and cultured hyperplastic human pterygial epithelial tissues. METHODS: Reverse transcriptase PCR and quantitative real-time PCR, along with immunohistochemistry and Western blotting, characterized TRPV1 expression patterns in pterygial and healthy conjunctival tissue, primary and immortalized pterygial cells (hPtEC), and primary and immortalized conjunctival epithelial cells (HCjEC). Imaging of Ca2+ and planar whole-cell patch-clamping evaluated TRP channel activity. An MTS assay measured cell metabolic activity and a cell growth assay monitored proliferation. RESULTS: Capsaicin (20 μM) and elevating bath temperature above 43°C activated Ca2+ transients more in hPtEC than HCjEC. Capsaicin induced corresponding changes in inward currents that were inhibited by 20 μM capsazepine (CPZ). Vascular endothelial growth factor (VEGF) also increased Ca2+-influx and induced corresponding inward currents more in hPtEC than in HCjEC, whereas CPZ (20 μM), BCTC (20 μM), or La3+ (500 μM) reduced these responses, respectively. Whereas epidermal growth factor (EGF) increased proliferation more in hPtEC than in HCjEC, VEGF had no effect on this response. Capsazepine suppressed hPtEC proliferation induced by EGF and VEGF, whereas it was cytotoxic to HCjEC. CONCLUSIONS: Mitogenic responses to EGF and VEGF are mediated through TRPV1 transactivation. Only in hPtEC do the increases in proliferation induced by EGF exceed those in HCjEC. Therefore, TRPV1 is a potential drug target whose clinical relevance in treating pterygium warrants further assessment.
EVALuna2:35348